Iowa Birdline update, April 25, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email for the Iowa Birdline update for April 25, 1994. Highlights include Cinnamon Teal, Marbled Godwit, Piping Plover and passerine migration. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed